2022
DOI: 10.32598/ijpcp.27.4.3123.1
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Persian version of Trait Emotional Intelligence Questionnaire in College Students

Abstract: Objective: The purpose of this study was to Standardize and evaluate the psychometric properties of Trait Emotional Intelligence Questionnaire (TEIQue) in the Persian adult population. Method: 551 students completed the Farsi version of this questionnaire, along with the Schutte Emotional Intelligence Questionnaire (SEIS) and the Neo-Five Factor Questionnaire (NEO-FFI). Results: The results of exploratory factor analysis, showed that the Persian version of the Trait Emotional Intelligence Questionnaire consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The authors, Schutte and colleagues, reported that the SSEIT items have an excellent internal consistency reliability (Cronbach's alpha α = 0.90), and good predictive validity (Pearson's product moment correlation r = 0.32, p < 0.01) (21). In the present study, the Persian (Farsi) translation version of the wholescale SSEIT had good internal consistency reliability (Cronbach's alpha α = > 0.75), and good internal consistency for the SSEIT subscales (Cronbach's alpha α = > 0.73-.0.78) (35).…”
Section: Schutte Self-report Emotional Intelligence Test (Sseit)supporting
confidence: 46%
“…The authors, Schutte and colleagues, reported that the SSEIT items have an excellent internal consistency reliability (Cronbach's alpha α = 0.90), and good predictive validity (Pearson's product moment correlation r = 0.32, p < 0.01) (21). In the present study, the Persian (Farsi) translation version of the wholescale SSEIT had good internal consistency reliability (Cronbach's alpha α = > 0.75), and good internal consistency for the SSEIT subscales (Cronbach's alpha α = > 0.73-.0.78) (35).…”
Section: Schutte Self-report Emotional Intelligence Test (Sseit)supporting
confidence: 46%
“…The psychometric characteristics of the Iranian version are as follows: Internal consistency coefficient=0.88 and re-test coeffi-cient=0.79. The correlation of the total score of the questionnaire with the score of the trait-state inventory is 0.68 and the total score of the BDI is 0.49, which indicates a good convergent validity (Dehshiri et al, 2009).…”
Section: Penn State Worry Questionnaire (Pswq)mentioning
confidence: 82%